SISTEM PENDUKUNG KEPUTUSAN PENENTUAN TEMPAT WISATA TERFAVORIT DI NIAS SELATAN DENGAN METODE WEIGHTED PRODUCT (WP) - Erni Agus Giawa; Zekson Arizona Matondang (UPPM, 2018)
Decision support system for determining the location of the favorite tourism object is an application that was intentionally built to facilitate the work of employees at the Department of Tourism in determining the place of favorite tourism objects, problems that occur in the process of determining the most favorite tourist objects such as subjective assessment and irrelevant actually so that it cannot be used as a basis for decision making. If this decision-making process is assisted by a computerized decision support system, it is expected that subjectivity in decision making can be reduced. Therefore, it is necessary to design a Decision Support System application using the Weighted Product method, so that later it will be able to produce an effective and efficient analysis.